THE ANALYTICAL DYNAMIC MODEL OF THE STRUCTURE OF THE INFORMATION SYSTEM CONDITION - Begimov Oktam Ibragimovich (Web of Journals Publishing, 2025)
The article describes the mathematical expression of the dynamic characteristics of the transmission properties of the object represented by the line he selects automatic control systems using real input and output variables and output variables of abstract types kosh represented by the differential equation.
Keywords: Information systems, selects the automatic construction metho intelligent, data mining, process your data, model evaluation and optimization, security, protection against unauthorized access, types of dynamic models, input-output and input-state-output model.